A MEG Study of Acute Arbaclofen (STX-209) Administration - Roberts, Timothy P. L.; Bloy, Luke; Blaskey, Lisa; Kuschner, Emily; Gaetz, Leah; Anwar, Ayesha; Ku, Matt; Dipiero, Marissa; Bennett, Amanda; Edgar, J. Christopher (Frontiers in Integrative Neuroscience, 2019)
Several electrophysiological parameters, including the auditory evoked response component M50/M100 latencies and the phase synchrony of transient and steady state gamma-band oscillations have been implicated as atypical (to various extents) in autism spectrum disorder (ASD). Furthermore, some hypotheses suggest that an underlying neurobiological mechanism for these observations might be atypical local circuit function indexed by atypical levels of inhibitory neurotransmitter, GABA. This study was a randomized, placebo-controlled, double-blind, escalating-dose, acute investigation conducted in twenty-five 14 to 18 year-old adolescents with ASD. The study assessed the sensitivity of magnetoencephalography (MEG) and MEGAPRESS “GABA” magnetic resonance spectroscopy to monitor dose-dependent acute effects, as well as seeking to define properties of the pre-drug “baseline” electrophysiological and GABA signatures that might predict responsiveness to the GABA-B agonist, arbaclofen (STX-209). Overall, GABA levels and gamma-band oscillatory activity showed no acute changes at either low (15 mg) or high (30 mg) dose. Evoked M50 response latency measures tended to shorten (normalize), but there was heterogeneity across the group in M50 latency response, with only a subset of participants (n=6) showing significant M50 latency shortening, and only at the 15 mg dose. Findings thus suggest that MEG M50 latency measures show acute effects of arbaclofen administration in select individuals, perhaps reflecting effective target engagement. Whether these subjects have a greater trend towards clinical benefit remains to be established. Finally, findings also provide preliminary support for the use of objective electrophysiological measures upon which to base inclusion for optimal enrichment of populations to be included in full-scale clinical trials of arbaclofen.